Construction of a model of endometritis in domestic rabbits using equine-derived pathogens and evaluation of therapeutic effect of sensitive drugs - Ding, Xuanpan; Cui, Xiao; Shi, Jinlian; Cheng, Xiaoli; Yao, Dan; Gao, Yujin; Zhang, Yong (Frontiers in Veterinary Science, 2023)
Pathogenic bacteria were isolated from the uterine lavage fluid of a mare with endometritis. After identification and purification, the pathogenic bacteria were injected into the uterus of rabbits to induce endometritis. Then, anatomical, blood routine, chemical examination, and histopathological examinations were performed on the rabbits. Rabbit uterus was collected, and quantitative polymerase chain reaction (qPCR) was used to detect the mRNA expression of inflammatory factors including IL-1β, IL-6, and TNF-α in the rabbit uterus. In addition, enzyme-linked immunosorbent assay (ELISA) was used to detect the uterine concentrations of the inflammatory factors IL-1β, IL-6, and TNF-α. Western Blot was used to detect the protein expressions of NF-kB, IkBα, and TNF-α in the NF-kB pathway. An antibiotic treatment group was also set up to verify the accuracy of the results. The clinical examination results showed that there was a significant increase of leukocytes in the blood of the rabbits in the model group (P < 0.01). The uterus was congested, enlarged, and purulent. The integrity of the uterine lining was destroyed, and there was a significant increase of lymphocytes in the uterus (P < 0.01). The qPCR and ELISA results showed that the expressions of the inflammatory factors IL-1β, IL-6, and TNF-α in the uterus of rabbits were significantly increased (P < 0.01). Western blot results showed that the inflammatory factors IL-1β, IL-6, and TNF-α play a role in promoting inflammation through the NF-kB pathway. The results of the test provide a simple, economical, and reliable means of studying the occurrence, development, prevention, and treatment of equine endometritis.